Miniaturized sample preparation strategies for the determination of N-nitrosamines in pharmaceutical products: A comprehensive review - Almir Custodio Batista Junior; Yuri Arrates Rocha; Andrea Rodrigues Chaves (Journal of Pharmaceutical and Biomedical Analysis Open)
N-Nitrosamines (NAs) are classified as potent mutagenic impurities, raising substantial concerns due to their presence in various consumer products, including pharmaceuticals products. The detection of NAs in valsartan-containing medicines in 2018 led regulatory agencies to establish strict guidelines for permissible levels in drug formulations. The standard-gold analytical techniques for NAs determination have been chromatographic techniques (liquid and gas chromatography) coupled with mass spectrometry system, which present higher sensibility and accuracy for target NAs. However, accurate determination of NAs in medicines remains challenging due to their trace-level concentrations and susceptibility to matrix effects, carryover, and contamination of the analytical instrumentation, emphasizing the need for robust sample preparation strategies. Traditional sample preparation methods, although effective, often involve high consumption of solvents, samples, and extraction phases, along with substantial waste generation. In response, miniaturized sample preparation techniques have emerged as sustainable alternatives, offering reduced solvent usage, minimal sample requirements, and lower energy consumption, all while maintaining analytical performance. These green approaches not only align with sustainable analytical practices but also enhance efficiency and environmental compliance in pharmaceutical analysis. This review provides a comprehensive overview of recent advancements in miniaturized sample preparation strategies for the determination of NAs in pharmaceutical products, highlighting their analytical merits and potential for regulatory adoption.